Inisiatif Keterlibatan Orangtua Dalam Pendidikan Anak: Konteks Pola Asuh - Siti Aika Rahayu; Dede Nurul Qomariah; Dede Nuraeni; Intan Sri Nenci (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
The involvement of parents in children's education has long been the focus of attention of practitioners, academics and policy makers in the field of education. Various research results have found that parental involvement contributes positively to children's education. The purpose of this study is to explore how the initiative of parental involvement in the context of parenting at home. Descriptive method with a qualitative approach is used in this study. The results of the study show that the initiative for parental involvement in children's education in the context of parenting is shown through 4 things, namely: parenting skills, family support, child development, and home environment conditions that support children's learning. In general, the initiatives for parental involvement in children's education in the context of parenting that we found tend to be authoritative. Authoritative parenting encourages children to be independent but still places boundaries and control over their actions. Verbal exchange is still allowed for parents to show warmth in parenting their children. This parenting pattern is motivated by a sense of responsibility from parents in raising their children. This sense of responsibility is then realized through parenting that is in line with the program at school. The background of past experiences also affects their parenting at home.